THE GEOLOGICAL ENVIRONMENT CHANGES AT DIFFERENT FLOODING TYPES IN UKRAINE - AKSOM, O.; ZAKHARII, N.; KORZHNEV, M.; KOSHLIAKOV, O.; YAKOVLIEV, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
The article discusses problems of the geological environment changes at different flooding types in Ukraine. Historical stages of mentioned flooding factors development, occurrence and approaches for their forecast are analyzed.